2019
DOI: 10.1097/md.0000000000013971
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis of cell-free RNA in amniotic fluid from women destined to develop preeclampsia

Abstract: Preeclampsia (PE) is a disorder specific to pregnancy characterized by new-onset hypertension and proteinuria after 20 weeks of gestation. There is no definite treatment for PE except delivery of the placenta. The purpose of this study was to elucidate the biological pathways involved in the development of PE and to discover a novel biomarker for PE by performing global gene expression analysis of amniotic fluid cell-free RNA.The participants were recruited from the Department of Obstetrics and Gynecology of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…In 2019, Jung et al [ 72 ] investigated global gene expression and the AF-cell-free-transcriptome associated with the development of PE during the second trimester to identify biological pathways involved in the pathogenesis of PE. They showed that genes associated with the ribosome pathway and immune-related pathway were enriched in the AF- cell-free-transcriptome of PE.…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…In 2019, Jung et al [ 72 ] investigated global gene expression and the AF-cell-free-transcriptome associated with the development of PE during the second trimester to identify biological pathways involved in the pathogenesis of PE. They showed that genes associated with the ribosome pathway and immune-related pathway were enriched in the AF- cell-free-transcriptome of PE.…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…The cell-free supernatant that remains upon removing the AF's cellular components reflects fetal well-being and pregnancy status 46 , 47 , 49 56 . Indeed, studies have described changes in the AF cell-free transcriptome in fetal genetic disorders, such as trisomy 18 50 , trisomy 21 49 , and Turner syndrome 52 , as well as in fetal growth restriction 54 and preeclampsia 55 . Others have investigated the association between the AF cell-free transcriptome and maternal factors such as race, obesity, and smoking status 51 , 56 , as well as neonatal morbidity 53 ; yet, the AF cell-free transcriptome in spontaneous preterm labor was not assessed in prior investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of AF cfRNA are not only limited to cells in amniotic uid [4]. The AF cfRNA could be in uenced by fetal sex [2], gestation age [2,[5][6][7], genetic disorders [1,[8][9][10][11], developmental disorders [12][13][14][15], maternal obesity [16], and preeclampsia [17]. Therefore analysis of the transcriptome for the AF cfRNA may provide feasible markers for organ development and fetal malformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment analyses of different expressed genes in abnormal fetus AF cfRNA include Gene Ontology analysis [13,23], Kyoto Encyclopedia of Genes and Genomes pathway analysis [17], and QIAGEN's Ingenuity Pathway Analysis (IPA) [23]. Gene Ontology analysis was the most frequent method used.…”
Section: Introductionmentioning
confidence: 99%